PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN TUMBUHAN AKAR KAIK-KAIK (Uncaria cordata (Lour.)Merr) TERHADAP KADAR TRIGLISERIDA SERUM TIKUS PUTIH (Rattus norvegicus) JANTAN - Dwi Pratiwi; Novia Sinata; Noveri Rahmawati; Meiriza Djohari (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Hypertriglyceridemia is a condition when there is an increase in triglyceride levels in the blood. Hypertriglyceridemia can cause heart problems. One of the plants that can be used as medicine is the root plant kaik-kaik (Uncaria cordata (lour.) Merr). This study aims to determine the effect of giving ethanol extract of kaik-kaik (Uncaria cordata (lour.) Merr) leaves on serum triglyceride levels of male white rats (Rattus norvegicus). The parameters used were serum triglyceride levels of male white rats induced by high fat feed, namely quail egg yolk as much as 10 ml/kgBB. This study used 18 male white rats which were divided into 6 groups with 3 rats per group. The normal group was fed only with rats and Na CMC suspension, the negative group was given high-fat feed induction and Na CMC suspension. The positive group was given high-fat feed induction and 0.9 mg/kgBB of atorvastatin suspension. The treatment group was given high-fat feed and a suspension of ethanol extract of kaik-kaik root leaves at doses of 100, 200, and 400 mg/kgBB as much as 1% of body weight given orally. The method used was colorimetric enzymatic using a Mindray® photometer (BA-88A) at a wavelength of 510 nm. Triglyceride level data on days 0, 15, 22 and 29 were analyzed by one-way ANOVA test and repeated ANOVA. The results showed that the ethanol extract of kaik-kaik root (Uncaria cordata (Lour.) Merr) leaves at doses of 100, 200 and 400 mg/kgBB had an effect in reducing serum triglyceride levels of male white rats (Rattus norvegicus) indicated by differences. which was significant (p <0.05) with negative control and showed activity to decrease triglyceride levels which was not significantly different (p> 0.05) with atorvastatin.